Future implementation of mobility as a service (MaaS): Results of an international Delphi study. (October 2020) - Jittrapirom, Peraphan; Marchau, Vincent; van der Heijden, Rob; Meurs, Henk
Highlights: The Delphi method is used to gather experts' opinions to address uncertainties surrounding future implementation of MaaS. We explore expert's preferences on the subject, their diverging opinions, and underlying motivations. We report new insights on implementation issues, such as vulnerabilities, opportunities, associated uncertainties, and responding actions. There are variations in the levels of agreement and the experts' individual's selection stability on the subject. The results are a useful reference point to support practitioners and researchers in MaaS planning. Abstract: Given the innovative nature of Mobility-as-a-Service (MaaS), various uncertainties are surrounding the possibilities for implementing MaaS. This includes uncertainties about alternative MaaS-system functionalities, about how the implementation of alternative MaaS systems might affect the overall transport system performance and about the preferences of stakeholders regarding alternative MaaS system implementation strategies. This paper contributes to this niche by collecting expert opinions about these uncertainties, using the Delphi method. The expert panel expected a fully-integrated MaaS to start operating in urban areas before 2020 and to expand to rural areas and nationally within the period of 2020–2030. In contrast to the common expectation that MaaS will attract regular car driver from their vehicles, our panel expected youth, current public transport users, and flexible travellers to be early adopters of MaaS. Transport operators are seen as the most important actors and the most preferred MaaS service integrator. Local authorities are expected to have an important role in enabling MaaS. The main objectives for implementing MaaS are to reduce car dependency and to provide a flexible and more customised transport system accessibility to the general public. The implementation of MaaS as a pilot project is considered the most preferred policy in the next phase. These findings largely support earlier reported findings on MaaS implementation. This study report new findings regarding the levels of consensus and how the experts changed their individual opinions in light of the group results on the studied topics. Regarding certain topics, such as the early market, there are higher levels of agreements among the panel with lower proportions of them changing their selections in light of the group results. Whereas in other topics, such as planning for future implementation, the level of agreement are lower with higher proportions of experts changing their selections. These two attributes can be combined to infer how certain the panel is on the topics studied. The study also provides new insights into the possible vulnerabilities and opportunities that can arise in relation to MaaS implementation, the associated levels of importance and uncertainty, and the possible responding actions. The experts also identified potential social issues and challenges in scaling-up the pilot. The findings of this study are of interest to practitioners and researchers in the field of MaaS planning and can be used to initiate a discussion among actors and stakeholders to formulate implementation plans for different MaaS concepts.